2010
DOI: 10.1007/s11240-010-9744-2
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced shoot organogenesis and regeneration in the common bean (Phaseolus vulgaris L.)

Abstract: Four cultivars of common bean (Phaseolus vulgaris L.) were tested for regeneration efficiency. Embryo axes from mature seeds were incubated on Murashige and Skoog or Gamborg media containing 6-benzyladenine (10 mg/l), without and with adenine hemisulphate (20 mg/l). Efficient regeneration was achieved when explants were incubated on Gamborg media amended with 6-benzyladenine, without adenine hemisulphate. This medium provided high regeneration efficiency in the four cultivars tested: Apetito G13637 (98-100%), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
1
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 19 publications
2
21
1
3
Order By: Relevance
“…This result, in agreement with Varisai Mohamed et al Mukeshimana et al 2013) where shoots were regenerated from embryonic axis and from calli from cotyledonary nodes and apical meristems (Arellano et al 2009), this system is based on the production of multiple buds from non-meristematic tissue. The regeneration efficiency that we report is high compared with the results obtained previously by Delgado-Sánchez et al (2006), Gatica Arias et al (2010), and similar to those reported by Kwapata et al (2012) and Quintero-Jiménez et al (2010).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This result, in agreement with Varisai Mohamed et al Mukeshimana et al 2013) where shoots were regenerated from embryonic axis and from calli from cotyledonary nodes and apical meristems (Arellano et al 2009), this system is based on the production of multiple buds from non-meristematic tissue. The regeneration efficiency that we report is high compared with the results obtained previously by Delgado-Sánchez et al (2006), Gatica Arias et al (2010), and similar to those reported by Kwapata et al (2012) and Quintero-Jiménez et al (2010).…”
Section: Discussionsupporting
confidence: 92%
“…Somatic embryogenesis and shoot regeneration from callus is difficult to obtain in common bean and more genotype dependent than direct organogenesis. There are several reports describing regeneration from embryonic axes for common bean (Veltcheva et al 2005;Arellano et al 2009;Gatica Arias et al 2010;Quintero-Jiménez et al 2010;Kwapata et al 2012). Despite the available information on P. vulgaris in vitro regeneration, none of the published protocols has been successfully used for common bean genetic transformation.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that cytokinins are necessary for plant cell division, in the induction of adventitious bud formation, in the growth of lateral buds and in the cell cycle control (van-Staden et al, 2008;Gatica Arias et al, 2010;Quintero-Jiménez et al, 2010). We added different BAP concentrations beginning with 2.25 mg l −1 to SRM and included a treatment with BAP-free SRM to form shoots from callus.…”
Section: Discussionmentioning
confidence: 99%
“…Gatica Arias et al (2010) developed a method for direct regeneration of commercially important common bean cultivars combining N6-benzylaminopurine and adenine sulphate and using embryonic axes as initial explant. Quintero-Jiménez et al (2010) improved the in vitro regeneration protocol published by Delgado-Sánchez et al (2006), substituting Murashige and Skoog (1962) salts for those proposed by Gamborg et al (1968). Recently, Mukeshimana et al (2013) optimized a multiple shoots regeneration system for four common bean cultivars; but this system was unsuccessful to regenerate transformed plants.…”
Section: Introductionmentioning
confidence: 99%
“…Following 4-weeks of culture on plant growth regulator-supplemented media, the adventitious shoots in this study continued to proliferate, showing no signs of senescence or necrosis. Furthermore, the shoots did not require additional transfer to shoot multiplication or elongation medium, which is a standard procedure (Chitra and Padmaja 2005;Kumar et al 2005;Quintero-Jiménez et al 2010;Raveendar et al 2009;Zhang et al 2008), and were subsequently transferred directly onto rooting medium, thereby eliminating the need for an additional multiplication or elongation phase. In terms of shoot production time, this technique is a more efficient and rapid method of deriving shoots than the indirect organogenesis protocol or the axillary bud culture previously reported (Dewir et al 2010;Shaik et al 2010b).…”
Section: Discussionmentioning
confidence: 99%